Efeito da carbonatação na microestrutura e nas propriedades mecânicas de material alcalinamente ativado à base de metacaulinita - Lima, Gabriel de Sá Teles e (2019)
Studies have searched to understand the mechanisms of development of the various pathologies inherent to Portland cement-based structures that compromise their mechanical performance in concrete structures. In this sense, several researches have been developed regarding alternative materials that may replace or be incorporated in the traditional concretes aiming at the mitigation of these pathologies. In this sense, the Alkaline Activated Materials (AAM) have interesting properties, especially in their performance in aggressive environments, such as supercritical carbonation such as CO2 saturated atmospheres. This work aims to evaluate the effects of carbonation in AAM based on metakaolinite through the analysis of microstructure and thermomechanical properties, when subjected to CO2 saturated atmospheres. For that, a carbonation chamber was developed from a metal pressure vessel, where manometers and sensors were coupled to carry out the monitoring of the atmosphere inside the chamber during the tests. The carbonation atmospheres were obtained from the CO2 supply through bottled gas and the sublimation of the solid carbon dioxide. Samples of AMM were made from three different Si/Al ratios in order to assess their influence on the behavior of samples exposed to saturated atmospheres. Then, samples of the formulation Si/Al ratio with the best result (Si/Al = 3.42 due to its higher mechanical strength (15.2 MPa) and better physical integrity after the carbonation tests), were made and subjected to 05 (five) carbonation atmospheres during 4 hours of testing. Reference samples (Portland cement) were used in the same submission conditions as the AAM. The results of the microstructural analyzes showed an increase in carbonate phases as the CO2 pressure inside the chamber was high, both for the CP and AAM-based pastes, and the AAM samples showed greater degradation in all kinds of atmospheres.